2018
DOI: 10.3390/su10124401
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Government Competition on Regional R&D Efficiency: Does Legal Environment Matter in China’s Innovation System?

Abstract: Local governments are encouraged to compete in R&D investments and activities in China’s innovation system. We aim to understand the influence of government competition on regional R&D efficiency. We are also interested in examining how the attributes of legal environment act as a moderating variable for the relationship between government competition and R&D efficiency. We developed Tobit spatial models with spatial panel data of 30 provinces of China in 2008–2016. The results show that: (1) There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…H3a, H3c, and H3d are rejected while H3b is strongly supported. This is consistent with most research results [3,52]. Excessive government subsidies have reduced the incentive for enterprises to innovate while mature technology markets are conducive to increasing innovation outputs.…”
Section: Hypothesessupporting
confidence: 91%
See 1 more Smart Citation
“…H3a, H3c, and H3d are rejected while H3b is strongly supported. This is consistent with most research results [3,52]. Excessive government subsidies have reduced the incentive for enterprises to innovate while mature technology markets are conducive to increasing innovation outputs.…”
Section: Hypothesessupporting
confidence: 91%
“…Wang et al [51] evaluated the industrial eco-efficiency of Fujian province in China with an SBM-DEA model. He et al [52] analyzed the impact of government competition on regional R&D efficiency through the DEA model. Dai et al [53] studied the spatial evolution of technological innovation efficiency and talents' sticky wages.…”
Section: Research On Innovation Efficiencymentioning
confidence: 99%
“…(2) Selection index of industrial innovation activity subsystem: select parameters according to the industrial technology innovation chain, namely, R&D investment intensity (X5), R&D full-time personnel (X6), digestion and absorption of imported technology expenditure (X7), and number of effective invention patents (X8), national or industry patent standard number (X9), and patent ownership transfer income and license income (X10) as indicators of single parameters [21,22].…”
Section: Selection Of Subsystem Indicatorsmentioning
confidence: 99%
“…They concluded that competition is a very significant trigger factor for the companies to generate innovative products. Parallel to them, Blank and Naveh (2018), He et al (2018), Moen, Tvedten, and Wold (2018) and Shi, Song, and Teng (2019) also underlined the importance of this situation for their studies.…”
Section: Literature Reviewmentioning
confidence: 85%